Synthesis and Photocatalytic Activity of Si-doped TiO2 Nanotube/SnS Hybrids for Environmental Decontamination - Ma, Ning; He, Hai-Yan (Micro and Nanosystems, 2023)
Background: Heterostructures with nanoscale sizes have great superiorities in photocatalytic environment decontaminant because of their efficient interface charge transfer and great surface area. Objective: This work reports the facile fabrication of nano-tubular TiO2 and Si-doped TiO2 (NTs) hybridizing SnS nanocrystallites and their high-efficient photocatalytic activity. Methods: The modified hydrothermal processes were used to synthesize the nanotubes. A chemical bath deposition process was used to hybridize SnS nanocrystalline with the nanotubes. Results: The fabricated nanostructures show wide light absorption in the UV-visible region. The SBET, light absorption, hydrophilicity, and photo-induced super hydrophilicity were enhanced by Si-doping and SnS modification. Moreover, high-efficient interface charge transfer was produced after the SnS modification and further enhanced by the Si doping because of band structure modulation. Conclusion: Thus, the Si-doped TiO2 nanotubes/SnS heterostructures showed remarkably enhanced photocatalytic and Fenton-like photocatalytic activity in dye wastewater treatment than the TiO2 NTs. This work suggests potential materials and their facile fabrication process for the photocatalytic application of environmental decontamination.
Keywords: photocatalytic properties